Orbital Fungal Myositis; A Case Report - Mohammad Moin, Sahar Khalid (Pakistan Journal of Ophthalmology, 2018)
To report a case of 20 years old female presenting with proptosis of the left eye and restricted medial gaze due to medial rectus fungal involvement in an immune competent patient. She underwent removal of the medial rectus followed by muscle transposition surgery few months later with satisfactory outcome. Key words: Orbital myositis, Proptosis, Corneal mucormycosis.